The flawed genius of William Playfair : the story of the father of statistical graphics - Bellhouse, D. R. (University of Toronto Press, 2023)
"A product of the Scottish Enlightenment, William Playfair (1759-1823) worked as a statistician, economist, engineer, banker, land speculator, scam artist, and political propagandist. It has been claimed--erroneously--that Playfair was a spy for the British government and ran a forging operation to print the paper money of the French Revolution. The Flawed Genius of William Playfair offers a complete account of Playfair's life, richly contextualized in the economic, political, and cultural history of the French Revolution and Napoleonic Wars. The book explores the many peaks and troughs of Playfair's career, ranging from moderate prosperity to bankruptcy and imprisonment. Through careful analysis, David R. Bellhouse shows that Playfair was neither a spy nor a forger, but perhaps briefly a one-time courier for a government minister. Bellhouse pieces together as complete a picture as possible of the forging operations supported by the British government and illuminates Playfair's lasting contributions in economics and statistics, where he is known as the father of statistical graphics. Disputing the misinformation about the man, The Flawed Genius of William Playfair highlights that the truth about Playfair's life is often more intriguing than the fictions that surround him."--